Oxidation and corrosiOn behavior of titanium aluminum nitride coatings by arc ion plating - 李明升 冯长杰 张志峰 王福会 (Transactions of Nonferrous Metals Society of China, 2006)
Composite metastable TiN and Ti1-xAlxN coatings with different Al content were deposited on 1Cr11Ni2W2MoV stainless steel for aero-engine compressor blades by arc ion plating. The results show that all coatings have a B1NaCl structure and the preferred orientation changes from （111） to （220） with increasing Al content; the lattice parameter of Ti1-xAlxN decreases with the increase of Al content. The oxidation-resistance of （Ti,Al）N coatings is significantly improved owing to the formation of Al-riched oxide on the surface of the coatings. The nitride coatings can significantly improve the corrosion-resistance of 1Cr11Ni2W2MoV stainless steel under the synergistic of water vapor and NaCI, and the corrosion-resistance becomes better when the Al content increases, because not only the quick formation of thin alumina layer prevents the further corrosion but also the formation of alumina seals the pinholes or defects in the coatings, which prevents the occurrence of localized nodules-like corrosion.